Harmonization of PPh 21 Calculations Before and After the Implementation of The Average Effective Rate for Employees of PT. Fisca Bisnis Solusi: JEL Classification: H24, H25, H26, K34, M41 - Ilham Z. Salle; Alifqha Retno Winarsih; Winarti Winarti; Nur Alimin Azis (Journal of Management and Administration Provision, 2026)
Harmonization of Income Tax Article 21 (PPh Article 21) calculations before and after the implementation of the Average Effective Rate (AER) on employees of PT. Fisca Bisnis Solusi. The research is motivated by the enactment of Government Regulation Number 58 of 2023 and Minister of Finance Regulation Number 168 of 2023, which introduced the AER as a new mechanism for calculating monthly PPh Article 21 starting in 2024. This policy was designed to harmonize tax regulations by simplifying calculation procedures while maintaining compliance with the progressive tax system stipulated in Article 17 paragraph (1) letter a of the Income Tax Law. This study uses a qualitative descriptive approach with a case study method. Data were collected through interviews, observations, and documentation related to employee payroll and tax calculations. The results show that the implementation of the Average Effective Rate creates harmonization between tax regulations and administrative practices by simplifying monthly tax calculations and reducing the administrative burden on companies. Although monthly tax deductions become more straightforward, the final tax liability is still reconciled in December to ensure consistency with the annual progressive tax system. Therefore, the application of the Average Effective Rate contributes to regulatory and administrative harmonization without changing the overall tax burden borne by employees.